FEATURES OF THE PROTECTION OF PERSONAL DATA AND OTHER INFORMATION DURING ARMED CONFLICTS - Sopilko, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to study the essence of personal data and the peculiarities of their protection during the period of martial law in Ukraine and to provide recommendations on the regulation of relevant issues. Research methods: this scientific paper was written by the author with the use of generally recognized methods of scientific knowledge, namely, analytical, formal, comparative-legal, systemic-structural, and the like. Results: the concept, essence, and features of personal data and related categories were analyzed, the problems of ensuring their reliable protection were pointed out, and proposals were made to overcome such difficulties by improving national legislation, in particular, by adopting European experience and harmonizing the current legal framework with EU standards. Discussion: the discussion takes place in this study regarding the peculiarities of the legal regulation of personal data protection during the full-scale invasion of the Russian Federation into Ukraine and methods of improving the level of such protection in the current situation.